Effects of structure and physical chemistry of resistant starch on short-term satiety. (November 2022) - Huang, Jiating; Chang, Ranran; Ma, Rongrong; Zhan, Jinling; Lu, Xiaoxue; Tian, Yaoqi
Abstract: The present study investigated the effects of structure and physical chemistry and of resistant starch on short-term satiety in mice using three types of resistant starch (RS): high-amylose maize starch (HMS, RS2), retrograded HMS (RS3), and octenyl succinic anhydride (OSA)-modified HMS (RS4). RS3 resulted in the greatest satiety, as indicated by the lowest food intake over 4 h, followed by RS4 and RS2. RS3 also yielded the lowest postprandial blood glucose peak, blood glucose fluctuation, and gastric emptying rate, which was conducive to the continuation of satiety. Structural and physicochemical analysis revealed that the three resistant starches differed significantly in terms of particle size, chain-length distribution, and swelling power, which were all significantly associated with short-term satiety (Pearson correlation analysis). These findings could provide a theoretical basis for designing raw materials for high-satiety-inducing foods for patients with type 2 diabetes and obesity. Graphical abstract: Image 1 Highlights: Type Ⅲ resistant starch (RS3) resulted in greater satiety than RS4 and RS2. RS3 caused stable postprandial blood glucose and the lowest insulin level. Satiety was positively correlated with the swelling power of resistant starch.